TINJAUAN ATAS FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH - Ari Usama (LEGAL OPINION, 2024)
The reality that occurs in the supervisory function of DPRD is still considered less than optimal due to a lack of understanding in interpreting and developing existing regulations by the executive, which makes many differences in perception in understanding this matter. This paper focuses on the regulations that must be considered in the implementation of the supervisory function of DPRDs, which seem to be very limited in providing services to the people they represent. Therefore, in order to create a good governance, it is necessary to pay attention to the existing regulations to be developed better. So that the DPRD can truly become an institution that represents the aspirations and hopes of the people it represents. Realitas yang terjadi dalam fungsi pengwasan DPRD masih di anggap kurang optimal karena kurangnya pemahaman dalam menafsirkan dan mengembangkan peraturan yang ada oleh para eksekutif, yang menjadikan banyak terjadi perbedaan presepsi dalam memahami hal tersebut. Dalam penulisan ini berfokus kepada regulasi yang harus di perhatikan dalam pelaksanaan fungsi pengawasan DPRD yang seakan-akan sangat terbatas untuk melakukan pelayanan kepada rakyat yang di wakilinya. Olehnya, guna menciptakan sebuah pemerintahan yang good gemenance maka perlu diperhatikan kembali peraturan yang telah ada untuk di kembangan lebih baik. Agar kemudian DPRD memang betul menjadi sebuah lembaga yang benar mewakili seluruh aspirasi dan harapan rakyat yang di wakilinya.